Effects of Social Identity, Self-Esteem, Schooling, and Age on Hope [Efectos de la Identidad Social, la autoestima, la Escolaridad y la Edad sobre la esperanza] - Garcia, Cirilo Humberto; Daniel-González, Leopoldo; Valle de la O, Adrián; Diaz, Héctor L.; Castro, Laura K.; Téllez, Arnoldo (Acción Psicológica, 2021)
Abstract The primary objective of this study was to analyze the direct explanatory power of social identity, schooling, and age on self-esteem, as well as the indirect effects of those variables (through the mediating variable self-esteem) on hope. A non-probabilistic sample composed of 657 persons from southern Nuevo Leon was recruited (mean age = 39.75 years; SD = 16.96). Structural equation modeling was used to analyze the effects, both direct and indirect, of the independent variables upon the dependent variables. With regard to hope, the model yields an explained variance of 37% (d ≥ 26% = large effect size) and shows well goodness-of-fit indices: χ2 / df = 2.618, GFI = .997, AFGI = .978, CFI = .995, NNFI = .995, NFI = .992, RMSEA = .048 (IC90%, .001, .100), and SRMR = .017. It is concluded that social identity, together with some contextual variables of a personal nature (for instance, age and schooling) is probably very important to explain the levels of self-esteem and hope Resumen El objetivo primario de este estudio fue analizar el poder explicativo de las variables identidad social, escolaridad y edad, directamente sobre la autoestima y los efectos indirectos de las tres primeras, a través de la autoestima, sobre la esperanza. Se realizó el estudio en una muestra no probabilística de 657 hombres y mujeres, con edad promedio de 39.75 años (DE = 16.96). Se usó modelamiento de ecuaciones estructurales para analizar los efectos, tanto directos como indirectos, de las variables independientes sobre las dependientes. Se encuentra que el modelo tiene una varianza explicada del 37% (d = ≥ 26% = tamaño del efecto grande) en esperanza, con buenos indicadores de bondad de ajuste: χ2/gl = 2.618; GFI = .997; AFGI = .978; CFI = .995; NNFI = .995; NFI = .992; RMSEA = .048 (IC90%, .000, .100), SRMR = .017. Se concluye que probablemente la identidad social, junto con algunas variables contextuales de tipo personal, como la edad y la escolaridad, es prioritaria para explicar la existencia de la autoestima y de la esperanza.